Active porosity in swelling shales: insight from the Callovo-Oxfordian claystone. Issue 3 (5th September 2018) - Belmokhtar, M.; Delage, P.; Ghabezloo, S.; Conil, N.
Abstract : In swelling shales, significant clay–water interactions take place along the faces of the smectite minerals contained in the clay fraction, giving rise to the distinction between free water and adsorbed water. Further insight was recently gained by means of microstructure investigations, showing that the hydration mechanisms of pure or compacted smectites also explain the hydration and swelling behaviour of the Callovo-Oxfordian claystone, a possible host rock for deep radioactive waste disposal in France. In this rock, the proportion of water molecules adsorbed in intra-platelet pores was estimated to be around 25% of the total porosity, with 75% of the porosity containing free water. On the basis of these findings, the data of high-precision poroelastic measurements conducted in an isotropic compression cell showed that the porosity to account for a proper calculation of Skempton's B coefficient is not the total porosity, but the 75% proportion of the porosity corresponding to free water. This conclusion is believed to be of some interest with respect to the prediction of the rock response around the disposals at great depth, given that hydro-mechanical numerical simulations are often carried out within the framework of poroelasticity.